SUBJECTORIENTED MASTER’S DEGREE PROGRAM FOR KAZAKHSTAN INDUSTRY - Iosif V. Breido; Victor V. Egorov; Alexandr M. Kochkin (Высшее образование в России)
Abstract. At Karaganda State Technical University at the expense of the National Fund of the Republic of Kazakhstan there has been developed and introduced a new subject-oriented master’s degree educational program «Robotics. Control systems». The program has been developed on the basis of practices of the leading world universities. In its implementation participate the wellNknown technical universities of Russia – the members of the international educational Internet Synergy project. The lecturers conduct the lessons both in the status of the invited professors for teaching separate sections of the program courses and also are engaged in teaching full courses in the network form within a term.Within the program implementation there have been used technologies of project training. Its distinctive feature is orientation to solving specific objectives, to developing and upgrading the enterprises, as well as availability of the tripartite contract between a higher education institution, an undergraduate and an enterprise with possibilities of the graduate employment. The program solves three problems: the implementation of projects that are needed for upgrading production; training of specialists who do not need an adaptation period at enterprise; the guaranteed employment of master’s degree program graduates.Thereby training of engineering personnel within the subjectNoriented master’s degree program in line with the Bologna Process is provided.